Investigation of structural, dielectric, ferroelectric and optical properties of SrTiO3 doped (K,Na)NbO3 ceramics - Rani, Prinka (My University, 2019)
All lead-based ceramics show excellent electromechanical properties but due to toxicity of lead researchers have focused their attention on lead free ceramics such as (BiNa)TiO3, (K,Na)NbO3 etc. (K,Na)NbO3 ceramics find applications for sensors, actuators, transducers and high energy storage. Samples of (1-x)(K,Na)NbO3-(x)SrTiO3 ceramics for composition x=0, 0.1, 0.2 were synthesized using solid-state route and samples were studied for structural, dielectric, ferroelectric and optical properties. Single phase (K,Na)NbO3 ceramics were obtained. On addition of SrTiO3 a coexistence of orthorhombic-tetragonal symmetry is observed. A decrease in grain size is also observed. The dielectric properties were studied in wide temperature range of 50oC to 500oC at frequency varying from 100Hz to 1MHz. Room temperature ferroelectric hysteresis loops were measured for all the synthesized compositions. Dependence of remnant polarization and coercive field on SrTiO3 concentration indicates decrease in energy loss and increase in energy storage density.
Keywords: Lead free ferroelectric; X-ray diffraction; P-E loop; optical studies; Dielectric studies